Caffeic acid phenethyl ester (CAPE) prevents formaldehyde-induced neuronal damage in hippocampus of rats - Ozdem Turkoglu, Asli; Sarsilmaz, Mustafa; Kus, Uter; Songur, Ahmet; Ozyurt, Huseyin; Akpolat, Nusret; Ogeturk, Murat (My University, 2007)
The aim of this study was to investigate the neurotoxicity of formaldehyde on hippocampus and the protective effects of caffeic acid phenethyl ester (CAPE) against these toxic effects. For this purpose, 21 male Wistar rats were divided into three groups. The rats in Group I comprised the controls, while the rats in Group II were injected every day with formaldehyde (FA). The rats in Group III received CAPE daily while exposed to formaldehyde. At the end of 8 days experimental period, all rats were sacrificed by decapitation. The brains of the rats were removed and the hippocampus tissues were obtained from all brain specimens. Some of the hippocampus tissue specimens were used for determination of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) levels. The remaining hippocampus tissue specimens were used for light microscopic and immunohistochemical evaluation. The levels of SOD, GSH-Px and MDA were significantly increased in rats treated with formaldehyde compared with those of the controls. Furthermore, in the microscopic examination of this group, formation of apoptotic bodies, pycnotic cells, and vacuoler degeneration areas were observed. However, decreased biochemical parameters were detected in the rats administered CAPE while exposed to formaldehyde. Additionally, cellular damage caused by formaldehyde was decreased, and structural appearance was similar to that of the control rats in this group. These biochemical and histological findings observed in all groups were also confirmed by the immunohistochemical evaluation. It was determined that formaldehyde-induced neuronal damage in hippocampus was prevented by administration of CAPE.
Keywords: Caffeic acid phenethyl ester; Formaldehyde; Hippocampus; Neurotoxicity; Rat